2016
DOI: 10.1075/lab.13047.kou
|View full text |Cite
|
Sign up to set email alerts
|

Language interaction effects in bimodal bilingualism

Abstract: The focus of the paper is a phenomenon well documented in both monolingual and bilingual English acquisition: argument omission. Previous studies have shown that bilinguals acquiring a null and a non-null argument language simultaneously tend to exhibit unidirectional cross-language interaction effects — the null argument language remains unaffected but over-suppliance of overt elements in the null argument language is observed. Here subject and object omission in both ASL (null argument) and English (non-null… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…These two conditions have been subject to investigation in many bilingual acquisition studies. As for bimodal bilingualism, research shows that crosslinguistic influence is observed in structures not predicted by such conditions (Lillo-Martin et al, 2010), and findings for the structures that satisfy these two conditions run counter to predictions (Koulidobrova, 2012, 2016). Recently, Language Synthesis (Koulidobrova, 2012, 2016; Lillo-Martin et al, 2012, 2014, 2016) has been proposed to account for the various language interaction effects observed in bimodal bilingualism (see the next section).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…These two conditions have been subject to investigation in many bilingual acquisition studies. As for bimodal bilingualism, research shows that crosslinguistic influence is observed in structures not predicted by such conditions (Lillo-Martin et al, 2010), and findings for the structures that satisfy these two conditions run counter to predictions (Koulidobrova, 2012, 2016). Recently, Language Synthesis (Koulidobrova, 2012, 2016; Lillo-Martin et al, 2012, 2014, 2016) has been proposed to account for the various language interaction effects observed in bimodal bilingualism (see the next section).…”
Section: Introductionmentioning
confidence: 98%
“…As for bimodal bilingualism, research shows that crosslinguistic influence is observed in structures not predicted by such conditions (Lillo-Martin et al, 2010), and findings for the structures that satisfy these two conditions run counter to predictions (Koulidobrova, 2012, 2016). Recently, Language Synthesis (Koulidobrova, 2012, 2016; Lillo-Martin et al, 2012, 2014, 2016) has been proposed to account for the various language interaction effects observed in bimodal bilingualism (see the next section). The proposal is based on MacSwan's (2000, 2005) accounts for code-switching, in which he argues for one computational system with separate lexicons and separate Phonetic Forms (PFs) for different languages.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We are also eager to consider further the possible role of priming in examples of synthesis (or the role of synthesis in priming), as suggested by Serratrice. Koulidobrova (2012Koulidobrova ( , 2016, in work that has contributed significantly to the development of the Synthesis model, showed how influence through abstract syntactic features may lead to sub-optimal overt or null pronoun usage, just as Serratrice expected. Koulidobrova also suggests ways to account for the perhaps unexpected differences between bimodal and unimodal bilinguals in this domain.…”
Section: Modest Goalsmentioning
confidence: 99%
“…In our target article, we presented the Language Synthesis model, following from and building on our previous work (Koulidobrova, 2012(Koulidobrova, , 2016Lillo-Martin et al, 2012;Quadros et al, to appear;and other works). We have been thinking about and developing this model for some time, but it is still in its early stages, still more of an ideal than a conclusion.…”
mentioning
confidence: 99%